Integrative Analysis Reveals a Molecular Stratification of Systemic Autoimmune Diseases. Issue 6 (26th April 2021) - Barturen, Guillermo; Babaei, Sepideh; Català‐Moll, Francesc; Martínez‐Bueno, Manuel; Makowska, Zuzanna; Martorell‐Marugán, Jordi; Carmona‐Sáez, Pedro; Toro‐Domínguez, Daniel; Carnero‐Montoro, Elena; Teruel, María; Kerick, Martin; Acosta‐Herrera, Marialbert; et al.
Abstract : Objective: Clinical heterogeneity, a hallmark of systemic autoimmune diseases, impedes early diagnosis and effective treatment, issues that may be addressed if patients could be classified into groups defined by molecular pattern. This study was undertaken to identify molecular clusters for reclassifying systemic autoimmune diseases independently of clinical diagnosis. Methods: Unsupervised clustering of integrated whole blood transcriptome and methylome cross‐sectional data on 955 patients with 7 systemic autoimmune diseases and 267 healthy controls was undertaken. In addition, an inception cohort was prospectively followed up for 6 or 14 months to validate the results and analyze whether or not cluster assignment changed over time. Results: Four clusters were identified and validated. Three were pathologic, representing "inflammatory, " "lymphoid, " and "interferon" patterns. Each included all diagnoses and was defined by genetic, clinical, serologic, and cellular features. A fourth cluster with no specific molecular pattern was associated with low disease activity and included healthy controls. A longitudinal and independent inception cohort showed a relapse–remission pattern, where patients remained in their pathologic cluster, moving only to the healthy one, thus showing that the molecular clusters remained stable over time and that single pathogenic molecular signatures characterized each individual patient. Conclusion: Patients with systemic autoimmune diseases can be jointly stratified into 3 stable disease clusters with specific molecular patterns differentiating different molecular disease mechanisms. These results have important implications for future clinical trials and the study of nonresponse to therapy, marking a paradigm shift in our view of systemic autoimmune diseases.